(untitled) (The International Journal for Scientific Research, 2024)
This paper utilizes Garfinkel’s ethnomethodology to investigate the role of the ‘Masjid’ in the lives of Muslims, focusing on how religious practices, particularly the concept of ‘Baraka’, influence individual experiences within the Masjid. Employing both descriptive and analytical approaches, it explores the multifaceted meanings of Islamic rituals and their impact on daily life, highlighting the Masjid’s significance beyond mere worship. By delving into the practical methods through which Muslims engage with religious spaces, this research reveals the intricate interplay between social order, cultural identity, and spiritual fulfilment. Ultimately, it emphasizes the importance of recognizing religious spaces in fostering community cohesion and individual well-being, advocating for further exploration of Muslim experience within the Masjid through an ethnomethodological lens.